Math Game for Early Childhood - sri maryani (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2019)
The purpose of this study was to introduce mathematical games in the form of introducing geometric forms through the game of tangram in early childhood in the Istiqamah Bandung Playgroup   The type of research used is classroom action research, carried out in collaboration with class teachers. The research subjects were 13 children, consisting of 7 boys and 6 girls. The object of research is the introduction of geometric forms through the game of tangram. The technique of collecting data uses observation, interviews and performance. The data analysis technique uses qualitative analysis. The indicator of success in this study is if the percentage of the ability to recognize geometric shapes in children has reached 81% with very good criteria. The results of the study showed a gradual increase in the introduction of geometric forms through the game of tangram. The introduction of geometric forms can be seen from the indicators mentioning geometric shapes, designating geometric shapes, making more than one geometric shape and telling the geometric shapes they are made. Mathematical games in early childhood through the introduction of geometric shapes on the tangram game in the implementation of the Pre-action on the indicators mention geometric shapes 41.5%, and in Cycle II it increases to 93%, the indicators designate geometric shapes in the implementation of the Pre-action 35%, Cycle II increased to 90%, the indicator made more than one Prat geometry form, 37.5%, Cycle II increased to 85,%. As well as on the indicators telling geometric shapes that made pre-action 41.5% in the second cycle to 87.5%. Keywords: Math game, Early Childhood